Vom "Kohlrabi-Apostel" zum "Bionade-Biedermeier" Zur kulturellen Dynamik alternativer Ernährung in Deutschland - Albrecht, Jörg (Religionswissenschaft und Religionskritik, 2022)
For Jörg Albrecht, the increasing problematisation of meat consumption and the revaluation of sustainable nutritional styles is the starting point for a reconstruction of the history of alternative nutrition in Germany from the perspective of religious studies. From organised vegetarianism in the 19th century to wholefoods and natural foods in the 20th century to the "organic boom" of the recent past, he traces and analyses the transformations of non-conformist innovations into supposed mainstream phenomena: What exactly was adapted and made compatible and how? What factors influenced the processes? With his synthesis, Albrecht makes a sound theoretical contribution to modelling cultural dynamics.